An Apology of a Campaigner in King’s “Letter from Birmingham Jail” - Ghimire, Rishiram (Bon Voyage, 2023)
This article examines Martin Luther King’s letter written in Birmingham jail in 1963 in defense to eight white clergymen’s public statement against King’s campaign for civil rights. While King as a campaigner is determined to establish just society in America white religious leaders are defending discriminatory practices of segregation as a decree. This letter has been evaluated from the perspective of Life Writing/Narrative, in which King’s letter in relation to his life and public issue with focus of common good is debated and discussed. This letter is an apology of King as a campaigner that defends against the indictment of the oppressors. In the letter of King, it can be found the examples of atrocities toward black community as the manifestation of whites’ prejudice of rights, which the civilized society cannot imagine and withstand. Black community cannot remain oppressed eternally and King’s letter of initiation is crucial to open the eyes of the oppressors and the oppressed that America needs change. This letter responds strongly to the question, ‘Why is the action of a campaigner justifi able?’